Agroindustrial co-products and waste cooking oil in the production of lipases by thermophilic Bacillus licheniformis SMIA-3 - Carvalho, Aparecida Selsiane Sousa; Cruz, Erica; Andrade, Vanessa Vicente Vieira; Serra, Josilene Lima; Martins, Marco Antonio; Martins, Meire Lelis Leal; Moraes, Luana Pereira de (Acta Scientiarum. Technology, 2022)
The present study investigated the potential lipase production for Bacillus licheniformis SMIA-3 using the agro-industrial co-products: orange flour (OF) and grape flour (GF) blend waste cooking oil (WCO). The OF was selected due to its best source for lipase production observed in preliminary tests. Therefore, OF was tested at different fermentation times at 50Â°C using the statistical design Central Composite Rotatable Design (CCRD) allied to the response surface. An optimal region was found with lipolytic activity of 0.349 U mL-1 with OF and WCO filters around (0.50% w v-1) and between (0.55 and 0.75% w v-1), respectively, and the fermentation time at the central point (42h). Data supplied a method to produce lipase using orange flour and frying oil, as a way to reuse these waste as feedstock to obtain employable lipase and lower production costs with biotechnological applications in industrial sector